Formulasi dan Karakterisasi Mutu Otak-Otak Ikan Kembung Jantan dengan Bahan Pengisi Tepung Ubi Jalar - Yakob, Maykel; Yusuf, Nikmawatisusanti; Naiu, Asri Silvana (The NIKe Journal, 2024)
This research aims to determine the formula for male mackerel brains (R kanagurta) using sweet potato flour filler (I batatas) with different concentrations and also to find out the quality characteristics of the selected male mackerel brains (R kanagurta) product. In this research, the concentration of sweet potato flour (I batatas) from the male mackerel brain formula (R kanagurta) was 5%, 10% and 15%. The data analysis used was Kruskall-Wallis and the selected formulation was determined using the Bayes test. The results of the research showed that sweet potato flour (I batatas) had an influence on taste and aroma. The analysis result of the selected formula was formula B (10%) sweet potato flour. Results of organoleptic quality analysis of selected products using several test criteria, namely appearance, aroma, taste and texture. The appearance value of 7.88 indicates that the brains of male mackerel fish are quite bright, clean, brownish white in color, without mucus, the aroma is 7.96. Based on this value, it can be seen that the panelists stated that the fish's aroma is quite strong, the taste is 7.56. According to this value, it can be seen It is said that the criteria for mackerel brains have a strong fish and sweet potato taste, and the texture of 7.88 corresponds to this value. It can be said that the selected male mackerel fish cake have a dense, compact and somewhat elastic texture.